Debye temperature of CaO under high pressure up to 65.2 GPa - Bioud, Nadhira (International Journal of Advanced Chemistry, 2023)
In the present work we used the experimental relative volume unit cell and the elastic stiffness constants measured by Speziale et al. (Journal of Geophysical Research, Vol. 111, (2006), pp. B02203 (12 pages)) using the Radial X-Ray Diffraction at high pressure from 5.6 up to 65.2 GPa to investigate the effect of high pressure on the bulk modulus, aggregate shear modulus, elastic wave velocities and Debye temperature of calcium oxide (CaO) ceramic material in cubic rock-salt (B1) phase. Our obtained values show that the bulk modulus increases monotonously with increasing pressure, while the aggregate shear modulus, the mean elastic wave velocity and the Debye temperature of CaO material varied non-linearly and non-monotonously with increasing pressure from 5.6 up to 65.2 GPa.